Laboratory analysis of 124 chronic lymphocytic leukemia cases: Single center study - Shams Salah Mahdi; Nuha Abd Ali Al-Sarai (Iraqi Journal of Hematology)
BACKGROUND: Chronic lymphocytic leukemia (CLL) is a disease characterized by an uncontrolled proliferation of malfunctioning mature B-lymphocytes. It represents a variable range of clinical presentation and prognoses. Understanding the demographic and cellular characteristics of CLL patients can aid in better disease management and treatment outcomes. OBJECTIVES: To identifying hematological parameters and patterns and potential markers that could assist in better diagnosis and of CLL in the local population. PATIENTS, MATERIALS AND METHODS: A retrospective analysis of 124 cases of newly diagnosed CLL was conducted. Data were collected from reports over 2 years (April 2022-April2024), including demographics, Hb levels, WBC counts, platelet counts and expression of CD markers (5, 19, 20, 23, 200, FMC7, LAIR1 and others) using flow cytometry on peripheral blood specimens. Based on FC findings, patients were categorized into two groups for better assessment; definite diagnosis CLL and possible diagnosis CLL; then further subdivided into poor prognosis CLL and good prognosis CLL. RESULTS: Male patients represented 59.5% of cases and females were 40.5% with a median age of 61 years at diagnosis. The mean Hb level was 109 ± 2 g/L, the mean WBC count was 58.0 ± 25.0 × 109/L, and the mean platelet count was 190 ± 40 × 109/L. CD5 was positive in 97.6% of cases, with CD23 in 96%. CONCLUSION: This study provides an overview of the demographic and cellular marker characteristics of CLL patients in FC unit. The findings underscore the heterogeneity of CLL immunophenotype and the importance of detailed characterization in improving patient management protocols; however, further research is warranted to correlate these findings with other parameters of disease burden and prognosis to optimize the therapeutic approaches for CLL patients.